IMPLEMENTATION OF CHARACTER DEVELOPMENT THROUGH ISTIGHOSAH HABITATING IN THE INSTITUT AGAMA ISLAM MA’ARIF NU (IAIMNU) METRO LAMPUNG - Ehwanudin Ehwanudin; M. Zainal Arifin; Mispani Mispani; Habib Sulton Asnawi; Muhammad Zaini (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
One of the habituation models that can strengthen an individual's spirituality so that he is able to become fully human in finding solutions and reflecting on himself is by reading istighosah. Sources of data in this paper were obtained through observation and interviews within a period of 4 months, starting from September to December 2020. The results of this study indicate that the reading of istighosah can be an alternative educational model that can shape the character of society. The academic community of IAIMNU Metro Lampung through the transformation of the Islamic ideology Ahlu sunah waljama'jamah Annahdliyah which has the principles of tawazun, tasamuh, ta'adul and amar ma'ruf nahi is mungkar. The success of this habituation can be seen in general from the development of the IAIMNU academic community which leads to the construction or development of character by practicing the principles of religious attitudes which are tawasuth, tawazun, tasamuh, and always looking for a middle way (moderate). Besides, this habituation becomes a satisfaction both physically and mentally for the perpetrators